Process Optimization and Kinetic Modeling of Quality of Fresh‐Cut Strawberry Cubes Pretreated by High Pressure and Osmosis. Issue 5 (4th October 2016) - Dermesonlouoglou, Efimia K.; Bimpilas, A.; Andreou, Varvara; Katsaros, George J.; Giannakourou, Maria C.; Taoukis, Petros S.
Abstract: The quality and preservation of strawberry can be improved by applying mild treatments such as osmotic dehydration and high pressure. The aim was to optimize treatment conditions based on mass transfer, water activity and quality data and model the effect of the process, combined with high pressure, on important quality attributes (sensory indices, anthocyanin, color, etc.) and microbial stability during subsequent refrigerated storage. Strawberry cubes were osmotically treated at preselected conditions (35C, 45 min) (OD) and by in‐pack cold‐pasteurization (600 MPa, 25C, 5 min) (Osmosed and High Pressured, OHP) and stored at isothermal (5–15C) and dynamic conditions ( T eff = 7.8C). Kinetics of quality change was studied and modeled as a function of storage conditions. Shelf life was significantly prolonged for both OHP and OD (up to 10 and 4 months at 5C, respectively) compared to untreated samples (7 days at 5C). Samples with L‐cysteine added in the OD solution exhibited an exceptional red color intensity and stability during prolonged storage. Practical Applications: Extension of the storage life of the delicate tissue of strawberry is a challenge and can be achieved with the application of mild, nonthermal pretreatments, such as osmotic dehydration (OD) and high hydrostatic pressure (HP). The goal is to optimize the OD operating conditions in terms of water activity and end product quality. This study also provides information on the effects of pretreatments on the main quality attributes and microbial stability during subsequent refrigerated storage. Based on the validated models established, shelf life extension for OD and OD/HP‐treated strawberry cubes can be predicted at any isothermal or dynamic conditions, and be compared to that of untreated fruit samples. It is concluded that the effective combination of OD and HP processing can be used for the production of superior, fresh‐like quality fruit‐cubes, with extended shelf life, stable under chilled conditions.